NERVE AND CARDIOVASCULAR OF THE COVID-19 VIRUS IMPACT ON SYSTEMS. CT AND MSGT METHODS IN DETECTING COVID-19 MODERN INFORMATION TECHNOLOGY ROLE IN MEDICINE - Sanjarbek Atakhanov; Abdusattorov Asilbek (Zeta Repository, 2023)
The article details the effects of the COVID-19 virus on the nervous and cardiovascular systems. Also, CT and MSGT methods for detecting COVID-19 modern information technology Its role in medicine has been researched.